High-Efficiency Inductive Charging For High Frequency Wireless Power Transfer - Chinda, F.E. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper aims to demonstrate the design which improves the performance of RF Wireless Power Transfer (WPT) and charging system on the ground which can extend the charging voltage up to S.5 V and 12V for the transmitter to emit a low-power radio waves at the frequency of 500 MHz to 900 MHz the efficiency of 93 and the resonant frequency of 700 MHz at the surrounding space diameter of 300 mm are obtained. Â© 2021 IEEE.